A chemical approach for the future of PLA upcycling: from plastic wastes to new 3D printing materials. Issue 22 (25th July 2022) - Shao, Lin; Chang, Yu-Chung; Hao, Cheng; Fei, Ming-en; Zhao, Baoming; Bliss, Brian J.; Zhang, Jinwen
Abstract : Chemical upcycling of PLA:  Ethanolamine cleaves polylactic acid to high purity N -LEA. N -LEA reacts with methacrylic anhydride (MAh) yielding crosslinkable DME. Simply combine DME with reactive diluent and photo-initiator to form a 3D printing resin. Abstract : As the demand for PLA increases, post-consumer disposal strategies must be carefully considered. While we would love to embrace a bioplastic future, we also need to tread carefully. Though PLA is widely claimed to be biodegradable, full degradation often requires conditions not typically found in landfills or industrial composting. Therefore, it will negatively impact the environment if treated carelessly. In this work, we report a simple PLA upcycling path to turn existing PLA wastes into new 3D printable materials within 48 hours. The ester bonds of PLA can be cleaved efficiently via aminolysis. The obtained monomeric compound was derivatized with methacrylic anhydride, which introduces double bonds and thus a cross-linkable monomer is obtained. In combination with a comonomer and initiator, a photocurable resin is produced. The resin can be fed into any commercially available photocuring 3D printer. The 3D printed parts derived from PLA wastes exhibit impressive performances with a tensile strength of 58.6 MPa, Young's modulus of 2.8 GPa, and glass transition at ∼180 °C. Our work demonstrates a new route to active upcycling of PLA while minimizing the need for disposal.